2009
DOI: 10.1097/aog.0b013e3181a1d2f5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Obesity on the Ultrasound Detection of Anomalous Fetuses

Abstract: With increasing maternal BMI, we found decreased detection of anomalous fetuses with either standard or targeted ultrasonography, a difference of at least 20% when women of normal BMI were compared with obese women. Anomaly detection was even less in pregnancies complicated by pregestational diabetes. Counseling may need to be modified to reflect the limitations of ultrasonography in obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(71 citation statements)
references
References 7 publications
2
65
2
2
Order By: Relevance
“…In the three obesity classes - class I (BMI 30-34.9), class II (BMI 35-39.9), and class III (BMI ≥40) - the detection rates were 48, 42, and 28%, respectively. The detection rate among obese women was thus slightly higher than in the present study [15]. …”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In the three obesity classes - class I (BMI 30-34.9), class II (BMI 35-39.9), and class III (BMI ≥40) - the detection rates were 48, 42, and 28%, respectively. The detection rate among obese women was thus slightly higher than in the present study [15]. …”
Section: Discussioncontrasting
confidence: 51%
“…The effect of maternal obesity on ultrasound detection of fetal anomalies has been studied by Aagaard-Tillery et al [14 ]and Dashe et al [15] in two low-risk US populations (n = 8,555 and n = 10,112, respectively). Both studies indicate a lower detection rate of anomalous fetuses among obese women compared to women with a normal BMI.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the sensitivity was lower in women with increased body weight (93.6%), which highlights an association of maternal body weight with the detectability of fetal malformations. Similar results were published in a study that investigated the sensitivity of prenatal ultrasound between 18 and 24 weeks of gestation in 1098 cases (25). The authors described sensitivities of 97% in women with a normal BMI that decreased to 75%-88% among obese women.…”
Section: Discussionsupporting
confidence: 72%
“…Wong et al [24] found that the anomaly detection rate in pregestational diabetic patients was lower than the nondiabetic population (30% vs 73%) and attributed this finding to the significantly higher BMI of the diabetic patients (29 vs 23 kg/m 2 ). Dashe et al [25] published their experience at a large tertiary care facility with regard to anomaly detection and maternal BMI. They reported decreased detection with increased BMI.…”
Section: Detection Of Fetal Anomaliesmentioning
confidence: 99%